2015
DOI: 10.1152/ajplung.00328.2014
|View full text |Cite
|
Sign up to set email alerts
|

Arginase inhibition prevents bleomycin-induced pulmonary hypertension, vascular remodeling, and collagen deposition in neonatal rat lungs

Abstract: -Arginase is an enzyme that limits substrate L-arginine bioavailability for the production of nitric oxide by the nitric oxide synthases and produces L-ornithine, which is a precursor for collagen formation and tissue remodeling. We studied the pulmonary vascular effects of arginase inhibition in an established model of repeated systemic bleomycin sulfate administration in neonatal rats that results in pulmonary hypertension and lung injury mimicking the characteristics typical of bronchopulmonary dysplasia. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 65 publications
1
38
0
Order By: Relevance
“…This divergence is consistent with our laboratory's own previous observations employing alternative interventions [e.g., therapeutic hypercapnia, arginase inhibition (15,44)] that were also efficacious in preventing inflammation and vascular remodeling, but not in preventing vascular hypoplasia or emphysematous lung structure. It appears, therefore, at least in bleomycinexposed neonatal rats, that inflammation and vascular remodeling are regulated by pathways distinct from those that regulate angiogenesis and alveologenesis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This divergence is consistent with our laboratory's own previous observations employing alternative interventions [e.g., therapeutic hypercapnia, arginase inhibition (15,44)] that were also efficacious in preventing inflammation and vascular remodeling, but not in preventing vascular hypoplasia or emphysematous lung structure. It appears, therefore, at least in bleomycinexposed neonatal rats, that inflammation and vascular remodeling are regulated by pathways distinct from those that regulate angiogenesis and alveologenesis.…”
Section: Discussionsupporting
confidence: 91%
“…The degree of increase in LTB 4 secondary to bleomycin exposure was small, which we speculate may have reflected a dilutional effect inherent to measurement in whole tissue. LTB 4 has been previously described to be predominantly produced by inflammatory cells, particularly activated macrophages and neutrophils (32,50), which are both present in abundance in the bleomycin-exposed lung (15,26,30,44). In the present study, we were unable to determine the cellular sources of LTB 4 , due to a lack of commercially available antibodies suitable for in situ immunostaining.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This occurs through HIF1α regulation of the NOS2/iNOS gene, and HIF-2α regulation of the Arg-1 and Arg-2 genes (21-25). The enzyme Arg-2 in particular has been implicated in reducing airway NO and promoting remodeling and collagen deposition in pulmonary arterial hypertension (PAH) patients (26,27). We found that hypoxic up-regulation of arg-1 and -2 was reduced in hypoxia-conditioned isolated murine primary pulmonary endothelial cells (Fig.…”
Section: Significancementioning
confidence: 83%
“…The causal link between pulmonary hypertension and NO homeostasis has been extensively documented (26,36), and this is reflected clinically in the finding that intrapulmonary nitrates, biochemical reaction products of NO in bronchoalveolar fluid, and exhaled NO are all diminished in human pulmonary hypertension (37,38). Interestingly, primary pulmonary endothelial cells isolated from PAH patients have substantially increased expression of arg-2 (27), which would be predicted to decrease available L-arginine and reduce NOS-derived NO formation.…”
mentioning
confidence: 99%